Who's who in the Greek world - Hazel, John (Who's who series., 2000)
From monarchs and poets to corrupt officials and traitors, this A-Z guide takes readers on a fascinating biographical tour of ancient Greece. Entries offer vivid portraits based on the latest research in the field and cover: Philosophers like Socrates and Plato -- Poets, including Sappho and Sophocles -- Monarchs and warriors from Alexander the Great to Epaminondas -- The memorably infamous, such as the traitor Ephalites and Alexander's corrupt treasurer Harpalus -- And many more. His accessible and enjoyable reference is an invaluable resource for students of literature and history, travelers, and anyone interested in Western Classical culture and heritage. Covering from 750 BC to the end of the Roman Empire, veteran classicist Hazel offers a biographical guide to the Greek and Hellenistic world. He considers philosophers, poets, monarchs and warriors, and memorable infamous figures such as Alexander's corrupt treasurer Harpalus. He includes a chronology, king lists, maps, and extensive cross-references, but no index.